Benzopyran derivatives from endophytic Daldinia eschscholzii JC-15 in Dendrobium chrysotoxum and their bioactivities. Issue 10 (19th May 2019) - Hu, Ming; Yang, Xue-Qiong; Zhou, Qing-Yan; Li, Shu-Quan; Wang, Bang-Yan; Ruan, Bao-Hui; Yang, Ya-Bin; Zhang, Zhuo-Xi; Zhou, Hao; Ding, Zhong-Tao
Abstract: Five new benzopyran derivatives (2 –6 ) and a new natural product (1 ) were isolated from endophytic Daldinia eschscholzii in Dendrobium chrysotoxum and determined as (R)-2, 3-dihydro-2, 5-dihydroxy-2-methylchromen-4-one (1 ), (2R, 4S)-2, 3-dihydro-2-methyl-benzopyran-4, 5-diol (2 ), (R)-3-methoxyl-1-(2, 6-dihydroxy phenyl)-butan-1-one (3 ), 7-O-α-d -ribosyl-5-hydroxy-2-methyl-4H-chromen-4-one (4 ), 7-O-α-d -ribosyl-2, 3-dihydro-5-hydroxy-2-methyl-chromen-4-one (5 ), daldinium A (6 ). These compounds were evaluated for their antimicrobial activity, anti-acetylcholinesterase, nitric oxide inhibition, anticoagulant, photodynamic antimicrobial activities and glucose uptake of adipocytes. Some compounds showed photoactive antimicrobial activities and glucose uptake stimulating activities. Abstract :